MM25: More Than Just a Cough: A Dual Diagnosis of Lung Carcinoma and Hidden Hookworm Infection - Alisa Hanum, Arba’eni @ Arbaen; Nurdiyana, Zakaria; Norashikin, Samsudin; Nurnabilah, Zainuddin; Romano, Ngui (2025)
Introduction: Chronic respiratory symptoms often raise suspicion for pulmonary tuberculosis (PTB), especially in high-prevalence regions. However, a broad differential diagnosis is essential, particularly when initial investigations return negative. This case illustrates the value of comprehensive assessment in uncovering multiple underlying pathologies in an apparently straightforward presentation. Case report: A 60-year-old man, a chronic smoker with no known medical history, presented with progressive breathlessness and a 3-month history of chronic cough, weight loss, and anorexia. He also reported right-sided pleuritic chest pain for two days, increasing fatigue and dizziness, suggestive of long-standing anaemia. Physical examination was unremarkable, but chest X-ray showed right middle zone opacity with pleural effusion. Initial microbiological investigations for Mycobacterium tuberculosis (MTB) were negative on auramine staining and culture. A thoracocentesis was performed and pleural fluid was sent for histopathology, which revealed metastatic small cell squamous carcinoma. Blood tests showed microcytic hypochromic anaemia, prompting stool microscopy, which showed hookworm ova. The stool specimen was then referred to Faculty of Medicine and Health Sciences, Universiti Malaysia Sarawak for further species identification via molecular analysis, which subsequently confirmed the presence of Necator americanus. Despite chronic parasitic infection, his eosinophil count was low, suggesting long-standing parasitemia. He was treated with albendazole and supportive therapy for respiratory symptoms. Despite appropriate interventions, the patient’s condition deteriorated and unfortunately, he succumbed to death. Discussion: This case underscores the importance of considering alternative diagnosis in chronic respiratory presentations, especially when MTB tests were negative. A multidisciplinary approach revealed not only advanced lung malignancy but also an overlooked parasitic infection contributing to chronic anaemia. Thus, highlighting the challenges in managing late-stage presentations with multiple coexisting conditions.